THE SIGNIFICANCE OF THE TEACHINGS OF THE GREAT THINKER ABU ALI IBN SINA IN EDUCATION OF CHILDREN TODAY - Mirzaeva M. M. (Journal Park Publishing, 2023)
Actuality. The importance of the thoughts of great thinkers in educating people of our time in the spirit of high moral qualities, in improving our society as a perfect person, in the development of our country, and in strengthening our independence. It is not for nothing that under the direct leadership of the President of the Republic of Uzbekistan: "National Program of Personnel Training", "Law on Education" and presidential decrees were reflected. The views and opinions of the President of the Republic of Uzbekistan Shavkat Mirziyoyev regarding the fundamental reform of the education system are noteworthy: Another important issue that always comes to our mind is the manners, behavior, and worldview of our youth. Today, times are changing rapidly. The ones who feel these changes more than anyone else are the youth... But at the same time let them not forget their identity at the moment. Let the call to know who we are and the descendants of great people always echo in their hearts and encourage them to stay true to themselves. What will we achieve this at the expense of education, education and only education."